Electron beam irradiated nanocomposite for gas barrier application - Anuar, Hazleen; Jamal, Nur Ayuni; Abdul Razak, Shamsul Bahri (2011)
Polyolefin and layered silicate nanocomposites are expected to replace metals and high performance engineering thermoplastics with lower cost in future. Development of multifunctional nanocomposite system with enhanced mechanical properties, oxygen permeability resistance and flame retardant required excellent structural characteristic. To obtain such characteristics, the right selection of crosslinking methods and fabrication techniques play an important role. Electron beam irradiation is a popular method of crosslinking instead of chemical crosslinking due to fast process, pollution free, simple, and suitable for synthesis and modification of polymeric materials without the need of toxic additives. In this project, high density polyethylene (HDPE) and ethylene-propylene-diene-monomer (EPDM) blend is filled with organophilic montmorillonite (OMMT). The nanocomposites systems were prepared via intercalation technique with different OMMT loading. Two types of crosslinking techniques were applied; maleic anhydride polyethylene (MAPE) and electron beam (EB) irradiated system. The effectiveness of these systems were then compared with control specimen and analyzed for its mechanical, thermal, gas barrier properties and morphological examinations. The mechanical tests revealed that control, MAPE and EB irradiated systems had attained the optimum mechanical properties at 4 vol% OMMT content. The introduction of 4 vol% organophilic montmorillonite (OMMT) was found to further enhance the barrier property of nanocomposites. EB irradiated system at dose rate of 100 kGy showed excellent mechanical, thermal and gas barrier properties with highest crosslinking degree which were proved by gel content analysis. X-ray diffraction (XRD) analysis confirmed the existence of delamination structure with MAPE and EB irradiation techniques based on the disappearance of characteristic peak. The degree of delamination was further investigated by transmission electron microscope (TEM). On the other hand, field emission scanning electron microscope (FESEM) revealed the stacking condition of OMMT particles was greatly reduced with crosslinking agents particularly with EB irradiated system as evidenced by finer surface.